Laparoscopic-Assisted Recipient Nephrectomy and Recipient Kidney Procurement during Orthotopic Living-Related Kidney Transplantation - Dimitri Mikhalski; Karl Martin Wissing; Renaud Bollens; Daniel Abramowicz; Vincent Donckier; Anh-Dung Hoang (Case Reports in Transplantation)
Advanced atherosclerosis or thrombosis of iliac vessels can constitute an absolute contraindication for heterotopic kidney transplantation. We report the case of a 42-year-old women with end-stage renal disease due to lupus nephritis and a history of bilateral thrombosis of iliac arteries caused by antiphospholipid antibodies. Occlusion had been treated by the bilateral placement of wall stents which precluded vascular anastomosis. The patient was transplanted with a right kidney procured by laparoscopic nephrectomy from her HLA semi-identical sister. The recipient had left nephrectomy after laparoscopical transperitoneal dissection. The donor kidney was orthotopically transplanted with end-to-end anastomosis of graft vessels to native renal vessels and of the graft and native ureter. Although, the patient received full anticoagulation because of a cardiac valve and antiphospholipid antibodies, she had no postoperative complication in spite of a short period of delayed graft function. Serum creatinine levels three months after transplantation were at 1.0 mg/dl. Our case documents that orthotopical transplantation of laparoscopically procured living donor kidneys at the site of recipient nephrectomy is a feasible procedure in patients with surgical contraindication of standard heterotopic kidney transplantation.